Dental Health Care In The Management Of Pain In Swelling Due To Abscess - Herawati Herawati; Asriawal Asriawal; Badai Septa Wahyudadi; Bedjo Santoso (ABDIGI : JURNAL PENGABDIAN MASYARAKAT KESEHATAN GIGI, 2023)
Fulfillment needs baseman can be given through giving care in a way planned in a period time certain in a way sustainable until finish problem is. Actions of care health teeth and mouth carried out by a person therapist teeth and mouth aim To help patient fulfil eight need base on existing problems _ in cavity mouth patient . Based on Riskesdas problem health teeth and mouth form gum swelling and/ or go out boils ( abscesses ) are still there Lots experienced by society , namely by 14%. Problem gum swelling and/ or go out boils ( abscesses ) in the city of Makassar were 17.41%. Problem the make need there is a care program health tooth For handling pain in swelling consequence abscess . Implementation foster care started with data collection , identification problems , priorities problems , plans program implementation , and program implementation . In program implementation there are: three phase inside it . Devotion This carried out at the dental clinic RSAU dr. Dody Sardjoto in patients who have indication painful Because swelling consequence abscess . Products provided _ in devotion This form development implementation management of dental healt who has customized with characteristics patient sufferer poured abscess _ in the Consequential Pain Management Module Abscess . Result of devotion This is level severity pain experienced by the patient sufferer abscess experience 75% drop after done action distraction . Deep conclusion devotion This namely the program that has been made For fulfil need patient that is development askepgilut who has customized with characteristics patient sufferer abscess .. Keyword : asuhan kesehatan gigi ; nyeri ; abses